Investigating the molecular orientation and mechanical properties characterization of drawn polypropylene fiber with different draw ratios using simulated microinterferograms of double refraction Pluta polarizing fringes - MA El-Morsy; Satam Alotibi (Results in Optics)
Simulated (duplicated and non-duplicated) microinterferograms of double refraction Pluta microscope in the case of drawn polypropylene fiber were presented. The duplicated and non-duplicated microinterferograms offer the possibility of mapping the optical and mechanical properties of drawn polypropylene fiber. These microinterferograms were automatically analyzed to investigate the effect of the drawing process on the molecular orientation function and the structural properties of polypropylene fibers. An empirical formula to correlate the birefringence of polypropylene fiber with the draw ratio was presented. The orientation angle, the orientation factors (f2(θ)Opt, f4(θ)Opt, f2(θ)c, and f4(θ)c), the number of chains per unit volume (Nm), the stress-optical coefficient (SOC), the segment anisotropy (SA), the optical configuration factor (Δa), the dielectric constant (ϕ), the dielectric susceptibility (η),the specific refractivity (ω), and other optical parameters were calculated using non-Gaussian statistical approximation. The comparison between calculated results in the case of Gaussian and non-Gaussian approximation was presented. The segment orientation distribution is an important key to understanding the relationship between the growth of a crystallite and the orientation angle, so we discussed it in detail inside the text. The constants of Mooney-Rivlin equation for polypropylene fiber were determined. In this study, we presented a new and simple formula for calculating the principal refractive indices of fully oriented polypropylene fibers. The obtained results give good qualitative agreement with previous experimental data for polypropylene fiber.